Reassessment of the taxonomic status of Craseomys and three controversial species of Myodes and Alticola (Rodentia: Arvicolinae) - Tang, Ming Kun; Jin, Wei; Tang, Ying; Yan, Chao Chao; Murphy, Robert W.; Sun, Zhi Yu; Zhang, Xiu Yue; Zeng, Tao; Liao, Rui; Hou, Quan Fen; Yue, Bi Song; Liu, Shao Ying (Zootaxa, 2018)
The genera Myodes (red-backed voles) and Alticola (mountain voles) appear to be sister taxa based on morphological similarities, but molecular analyses fail to resolve them as monophyletic genera owing to the uncertain taxonomic status of Craseomys and Phaulomys. As a result of incomplete sampling of related specimens, ongoing controversies on the taxonomic positions of several generic and specific taxa necessitate further clarifications. Herein, we combined molecular, morphometric, and geometric morphometric approaches to analyze 217 specimens of 10 taxa of Myodes and Alticola systematically. We sequenced three genes (Cytb, COI, GHR) de novo from specimens with fresh tissues, and published sequences for M. shanseius and A. stoliczkanus for the first time. Based on this new molecular dataset, we produced phylogenetic trees using Bayesian inference, maximum likelihood, and maximum parsimony approaches. Our molecular and morphological analyses both identified three primary clades within Myodes and Alticola. The Craseomys–Phaulomys clade consistently separated from Myodes sensu stricto (s. str.) and Alticola s. str.–Platycranius. Our results support the resurrection of the genus Craseomys and the treatment of Phaulomys as its junior synonym. As Craseomys shanseius clustered with C. rufocanus in three gene phylogenies and this assessment was congruent with morphological results, we assigned C. shanseius to a subspecies of C. rufocanus. Specimens from one sampling site in Pulan County of Tibet possess M3 patterns typical of A. stoliczkanus and A. stracheyi, despite clustering together in matrilineal genealogy. Thus, we tentatively assigned A. stracheyi as a junior synonym of A. stoliczkanus. Our analyses confirmed the validity of A. semicanus and unambiguously distinguished it from A. argentatus by the ratio of tail length to head–body length, color of tail and feet, M3 pattern, and distribution.